AL-FAIL DAN BEBERAPA PERMASALAHANNYA DALAM BAHASA ARAB - Kasmiati Kasmiati (Hunafa: Jurnal Studia Islamika, 2007)
In Arabic, a fa’il is an ism marfu’ that occurs before its fi’il. Some of fa’ils are zhahir and some are mudhmar. A fa’il exists only whenever there is a fi’il. However, there is a fi’il that must be omitted from its fa’il since there is a sign denotes it. A fa’il has seven ahkam. This article discusses the seven ahkam al-fa’il in Arabic. Kata Kunci:  Ahkam al-Fail, fa’il zhahir, fa’il mudhmar, ahkam, mudzakkar dan muannats